Exploring Disaster Threats and Adaptation in the Urir Char Union of Sandwip lsland, Bangladesh - Nabila, Irtifa Alam; Tazwar, Mahir; Muna, Tahmida Sarker; Pal, Srity (The Jahangirnagar Review, 2024)
Being isolated from the mainland, Urir Char regularly faces numerous disaster threats. This study intends to explore the disaster threats and adaptation strategies of the island community of Urir Char union in Sandwip upazila, Chittagong. Field observations, focus group discussions, key informant interviews, and in-depth interviews were done to obtain primary data. Participatory Rural Appraisal (PRA) techniques such as hazard lists and seasonal hazard calendar aided in determining prevalent disaster threats and their severity based on local people’s perspectives. Coastal erosion, cyclone, and storm surge were regarded as the most damaging hazards in the research area. Some sociodemographic factors exacerbated the risks that existed in the area before. Moreover, it has been tried to find out available local adaptation strategies using PARA (protect, accommodate, retreat or avoid) framework. The char dwellers practice a variety of adaptation strategies, including raising the pond boundary, constructing a levee in front of the house, plantation around houses, relocating to a new location, and so on. Approximately 60% of those who participated in the survey had been relocated at least four times from their place of birth. Considering a few criteria such as effectiveness, implementation ability, relevance to vulnerability, suitability for future climate instability, and financial feasibility, it has been assessed that local adaptation practices are inadequate for a sustainable hazard management strategy. Overall, government assistance is required for costly structural adaptation measures in addition to existing non-structured measures to protect the union.